Copolymer Brush-Based Ultralow-Fouling Biorecognition Surface Platform for Food Safety - Vaisocherová-Lísalová, Hana; Surman, František; Víšová, Ivana; Vala, Milan; Špringer, Tomáš; Ermini, Maria Laura; Šípová, Hana; Šedivák, Petr; Houska, Milan; Riedel, Tomáš; Pop-Georgievski, Ognen; Brynda, Eduard; et al. (Analytical chemistry, 2016)
Functional polymer coatings that combine the ability to resist nonspecific fouling from complex media with high biorecognition element (BRE) immobilization capacity represent an emerging class of new functional materials for a number of bioanalytical and biosensor technologies for medical diagnostics, security, and food safety. Here, we report on a random copolymer brush surface - poly(CBMAA-ran-HPMAA) - providing high BRE immobilization capacity while simultaneously exhibiting ultralow-fouling behavior in complex food media. We demonstrate that both the functionalization and fouling resistance capabilities of such copolymer brushes can be tuned by changing the surface contents of the two monomer units: nonionic N-(2-hydroxypropyl) methacrylamide (HPMAA) and carboxy-functional zwitterionic carboxybetaine methacrylamide (CBMAA). It is demonstrated that the resistance to fouling decreases with the surface content of CBMAA; poly(CBMAA-ran-HPMAA) brushes with CBMAA molar content up to 15 mol % maintain excellent resistance to fouling from a variety of homogenized foods (hamburger, cucumber, milk, and lettuce) even after covalent attachment of BREs to carboxy groups of CBMAA. The poly(CBMAA 15 mol %-ran-HPMAA) brushes functionalized with antibodies are demonstrated to exhibit fouling resistance from food samples by up to 3 orders of magnitude better when compared with the widely used low-fouling carboxy-functional oligo(ethylene glycol) (OEG)-based alkanethiolate self-assembled monolayers (AT SAMs) and, furthermore, by up to 2 orders of magnitude better when compared with the most successful ultralow-fouling biorecognition coatings - poly(carboxybetaine acrylamide), poly(CBAA). When model SPR detections of food-borne bacterial pathogens in homogenized foods are used, it is also demonstrated that the antibody-functionalized poly(CBMAA 15 mol %-ran-HPMAA) brush exhibits superior biorecognition properties over the poly(CBAA).
Keywords: akrylové pryskyřice; Wettability; akrylamidy; Antibodies; protilátky; Nanoparticles; Acrylic Resins; Acrylamides; smáčivost; Biofouling; Escherichia coli; Food; bezpečnost potravin; zlato; Salmonella typhimurium; nanočástice; Gold; Food Safety; potraviny; bioznečištění